Pengembangan Potensi Wisata Air Terjun Modern Dan Kuliner Lokal Melalui Traveling and Food Sebagai Sumber Pendapatan Masyarakat - Yusnaini Ismail; Yessy Syahradesi; Yusnika Damayanti; Halimatussakdiyah Lubis (Utan Kayu Publishing, 2022)
Lawe Dua Village, Kutacane has the potential of a multi-story waterfall which is a tourist attraction for the community during holidays. However, there has been no renovation of the location of the waterfall after the 2019 flood, garbage is scattered, there are no public toilets and prayer rooms, there are no food and beverage sellers, and people who work as farmers have experienced a decrease in income due to the impact of Covid-19. This condition worsens the community's economy. The purpose of this community service activity is to introduce the potential for nature tourism and regional culinary specialties throughout Indonesia through the Hy-FooT (Healthy Food and Traveling) platform, increase the independence of community entrepreneurs, stimulate community preparedness to face flood disasters, and preserve nature and develop fostered villages as a pilot village that utilizes an online business platform in the tourism and culinary fields. The method of implementing this activity includes socializing activities, forming and fostering groups, disseminating knowledge, developing and simulating the use of the Hy-FooT platform, monitoring and evaluating program sustainability. The results of the activity are 68% of the community using the Hy-FooT platform, the formation of youth groups for nature conservation and culinary, 55% of culinary groups as sources of income, collaboration with the Village Head of Lawe Dua, the Agriculture Service, and the Southeast Aceh Regional Disaster Management Agency, as well as follow-up on sustainability. business through Hy-FooT.